Exploring the Emergence of Chemistry in Preschool Education: A Qualitative Perspective - Nikolaos Christodoulakis; Karina Adbo (MDPI AG, 2024)
The objective of this study was to deepen our comprehension of how children develop understanding in the field of science, particularly in chemistry. Using the framework theory as a theoretical lens enabled a focus on emergence as a dynamic change and transition. According to the framework theory, children's science learning involves a wide range of intuitive and counterintuitive scientific concepts related to ontological and epistemological perspectives. How children transition from everyday to scientific thinking during their early years of education is influenced by ontological and epistemological stances. The objective of this study is to introduce science content-including chemical concepts to preschool children-by utilizing a play-based learning approach in a longitudinal study. The exploration of verbal and non-verbal material, specifically pertaining to chemical content and individual differences, involved implementing educational experiments and real-life or animated zooming-in videos. The results indicated a well-established physical ontological framework utilized for the systematic interpretation of submicroscopic phenomena.